1988
DOI: 10.1002/anie.198804171
|View full text |Cite
|
Sign up to set email alerts
|

Weak Intramolecular Bonding Relationships: The Conformation‐Determining Attractive Interaction between Gold(I) Centers

Abstract: AuAu distances of only 3.000 Å in the complex 2 are convincing evidence for the existence of attractive interactions between Au1 centers. 2 is formed from 1 and [(CO)AuCl] with rotation of a CP bond. 1, Ph instead of Me, is sterically too strongly hindered for this reaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
128
1
2

Year Published

1994
1994
2015
2015

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 286 publications
(139 citation statements)
references
References 16 publications
8
128
1
2
Order By: Relevance
“…If the gold atoms are further apart and attached to a flexible molecular skeleton, their interaction leads to the adoption of unusual conformations which allow the mutual approach to reach the optimum equilibrium distance (ca 3 Å) (9). This effect was found in a large number of molecules where two or more X-Au-Y units are, for example, at the ends of hydrocarbon chains: a folding into the cis-conformations is observed which brings the ends into close proximity, and the ends are thus fixed in a non-standard configuration by Au-Au bonding (2).…”
Section: Intramolecular Aurophilic Interactions Between Distant Gold(mentioning
confidence: 99%
See 1 more Smart Citation
“…If the gold atoms are further apart and attached to a flexible molecular skeleton, their interaction leads to the adoption of unusual conformations which allow the mutual approach to reach the optimum equilibrium distance (ca 3 Å) (9). This effect was found in a large number of molecules where two or more X-Au-Y units are, for example, at the ends of hydrocarbon chains: a folding into the cis-conformations is observed which brings the ends into close proximity, and the ends are thus fixed in a non-standard configuration by Au-Au bonding (2).…”
Section: Intramolecular Aurophilic Interactions Between Distant Gold(mentioning
confidence: 99%
“…Some molecules of this type were thus found to adopt unusual conformations, in which the gold atoms can become nearest neighbours (9). The gain in stability through these non-classical interactions was obviously also the reason for unexpected multiauration processes which lead to a gathering of gold atoms at certain functions of a substrate (5, 10).…”
mentioning
confidence: 99%
“…Theoretical studies have shown that the aurophilic interaction is the result of correlation effects that are enhanced by relativistic effects [7,8]. The aurophilic interactions between the closed-shell Au(I) centres are important in determining the solid state structures of many gold(I) compounds and contribute to the chemical and physical properties of these complexes [1][2][3][4][9][10][11][12][13]. The distance between two interacting gold atoms in compounds showing aurophilic interactions is less than 3.6 Å.…”
Section: Introductionmentioning
confidence: 99%
“…Au interaction, have shown that the strength of the attractive aurophilic interaction is comparable to that of hydrogen-bonding: ca. 7-11 kcal/mol (20,21). In cases where multiple Au ...…”
Section: For Those Interested In the Luminescence Of Gold(i) Complexementioning
confidence: 99%